Binge drinking: A review and research agenda. Issue 1 (26th September 2022) - D'Alessandro, Steven; Carter, Leanne; Webster, Cynthia
Abstract: Binge drinking is a wicked social problem associated with poor health and safety outcomes. However, most research on binge drinking occurs outside consumer research and marketing. This paper presents a systematic review of the contributions of key disciplines (Health, Marketing, Psychology, Economics, Management, Social Science, and Sociology) to the understanding of binge drinking. Using the theory, context, characteristics and methods (TCCM) framework, we find the need for more theoretical investigation in binge drinking research and more research conducted outside western countries. A wide set of independent factors has been included in binge drinking research, but few studies consider mediating and moderating variables. Methods used vary across disciplines and those used are mainly descriptive research, regression, and experiments. We conclude that whilst progress in this field is evident much needs to be done for greater generalizability and robustness of findings.